The acute effect of static stretching on static balance and vertical jump in volleyball players - Moreira Umaña, Jean P. (2016)
Purpose: To determine the acute effect of 20-s SS on SB and VJ in professional Costa Rican volleyball players. Methods: Participants were 10 female (21 ± 2.40 yr.) and 10 male (20.60 ± 3.06 yr.) volleyball players. Participants were randomly assigned a control (CON) and experimental (EXP) conditions. SB and VJ were measured before (pre-test) and after (post-test) each condition using the Modified Clinical Test of Sensory Interaction on Balance (mCTSIB) on a Wii Balance Board for SB (displacement of the center of pressure, CoP) and the countermovement jump test for VJ. The EXP consisted of 7 lower-body muscles SS exercises performed during 20-s. The CON condition consisted on quiet sitting. Three-way ANOVA (gender x treatments x measurements) and follow-up analysis were used for the SB and VJ variables. Results: A significant two-way interaction was found on the mCTSIB open eyes test on the board (OEB) (p < 0.05). Post hoc analysis showed a higher displacement of the center of pressure (CoP) in the EXP (45.2 ± 7.8 cm) than in the CON (44.0 ± 6.4 cm) condition. A significant three-way interaction was found on the mCTSIB closed eyes test performed over a flexible surface on the board (CEFB) (p < 0.05). A higher displacement of the CoP was found in the EXP (68.4 ± 13.6 cm) compared to the CON (67.3 ± 12.8 cm) condition. Males showed more displacement of the CoP than females in the EXP condition (71.1 ± 14.0 cm vs. 65.7 ± 13.0 cm; p < 0.05), and females showed more displacement of the CoP before than after treatment (68.1 ± 13.9 cm vs. 65.7 ± 13.0 cm; p < 0.05). Males in the EXP condition showed higher displacement of the CoP (71.1 ± 14.0 cm) than males in the CON condition (72.6 ± 11.9 cm; p < 0.05). No significant interactions or main effects were obtained on the mCTSIB closed eyes test performed on the board (CEB), open eyes with flexible surface on the board (OEFB), and VJ. Conclusions: A 20-s SS exercises on lower-body muscles negatively affects SB on the OEB and OEFB conditions, without any gender distinction. The SS exercises did not affect SB in the CEB condition and VJ. Males are more unbalanced than females in the CEFB after SS exercises.